The Mabinogi effect: the mythologization of the nonhuman in re-imaginings of medieval literature - Bartels-Bland, C (2018)
This thesis studies the mythologization of the nonhuman in re-imaginings of the Middle Welsh texts Pedeir Keinc Y Mabinogi (the Four Branches of the Mabinogi). The texts considered range from the first complete translation into English by Lady Charlotte Guest in the mid-nineteenth century to the most recent twenty-first-century version, encompassing a corpus of ninety-four re-imaginings in both English and Welsh. Previous studies on re-imaginings of the Mabinogi have consistently worked from the premise that the texts are myths, part of a mythology, or remnants of myths. Their starting point has thus not been the medieval texts themselves; rather, it has evolved from the mythologization which surrounds the Mabinogi in popular culture. This thesis investigates the consequences of approaching the Mabinogi as myth, which is here termed the Mabinogi Effect. Through this perception of a mythic narrative, the writers of the re-imaginings, in their turn, create and propagate their own myth of the Mabinogi. As the chapters of this thesis move through the different elements of the Mabinogi Effect, they reveal that the idea of a specific nonhuman concept plays a fundamental function in the creation of the myth. The nonhuman is not simply animal or landscape, but encompasses nature, super-nature and the artificial, bridging the divide between cyborgs and goddesses. It is a very specific idea of the nonhuman which pervades the corpus of re-imaginings. The simultaneous fear of and fascination with this multifarious nonhuman, this thesis argues, can reveal the specific impulses which lie behind each re-imagining. Chapter One discusses the nonhuman otherworld and its otherworldly creatures and deliberates the transferral of otherworldliness to Wales itself in the context of nineteenth-century views of Wales and the perceived nonhumanness of the Welsh. Chapter Two considers the Welsh language and its link to the nonhuman, which the corpus creates through the use of place-names. These place-names are discussed in the context of the two-fold status of the Welsh language, as a fabled, ancient tongue on the one hand, and as a political and symbolical tongue on the other. Chapter Three turns to the nonhuman in the form of human-animal relationships and human to animal transformations, the analysis of which reveals the simultaneous anxiety and fascination with the nonhuman which dominates the corpus. Chapter Four examines the conception of Blodeuwedd – the woman created out of flowers and later turned into an owl in the Fourth Branch – and the significance of her simultaneous humanness and nonhumanness for the re-imaginings. This thesis concludes that the Mabinogi myth has been created, upheld and encouraged by generations of re-imaginings out of two particular desires. First, in order to establish and propagate a national Welsh body of myths; and second, to facilitate the appropriation of the stories outside of Welsh literary culture. The specific nonhuman which stands at the centre of this corpus is fashioned to further these precise narratives. This analysis offers an alternative view to the idea that the popularity of the Mabinogi derives from its human and moral elements.